Pengaruh Ukuran Perusahaan, Struktur Aset, Profitabilitas dan Likuiditas Terhadap Struktur Modal Pada Perusahaan Consumer Goods Yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019 - Putri Eka Permatasari; Rahmawati, Aryani Intan Endah (Journal of Economics and Business Research (JUEBIR), 2023)
The aim of this research is to determine the influence of company size, asset structure, profitability and liquidity on capital structure. This research uses quantitative data obtained from secondary data. Data was obtained and downloaded via the website www.idx.co.id with a sample data collection technique using the purposive sampling method. The population of this research was 24 Consumer Goods companies in 2015-2019. and the sample for this research is 120 samples. Data analysis using outlier test analysis, descriptive statistical analysis, panel data regression analysis, classical assumption test and panel data multiple regression analysis. The results of this research show that company size has no effect on capital structure, while asset structure, profitability and liquidity have an effect on capital structure